S100P Expression Is a Novel Prognostic Factor in Hepatocellular Carcinoma and Predicts Survival in Patients with High Tumor Stage or Early Recurrent Tumors - Yuan, Ray-Hwang (Public Library of Science, 2013)
The calcium-binding protein S100P is expressed in a variety of human cancer cells and is important in cancer cell growth and invasion. Using differential display, we found S100P is overexpressed in human hepatocellular carcinoma (HCC). We examined the expression of 305 unifocal, primary HCC tumors using immunohistochemistry. The S100P protein was expressed in 173 of the 305 (56.7%) HCC tumors. The expression of S100P correlated with female sex (P = 0.0162), high serum α-fetoprotein level (P = 0.0001), high tumor grade (P = 0.0029), high tumor stage (P = 0.0319), the presence of the p53 mutation (P = 0.0032), and the absence of the β-catenin mutation (P = 0.0489). Patients with HCC tumors that expressed S100P were more likely to have early tumor recurrence (ETR) (P = 0.0189) and lower 5-year survival (P = 0.0023). The multivariate analysis confirmed that S100P expression was an independent prognostic factor in HCC. The combinatorial analysis showed an additive unfavorable prognostic interaction between S100P expression and the p53 mutation. In contrast, the β-catenin mutation was associated with better prognosis in both S100P-positive and -negative HCCs. Furthermore, S100P expression was a predictor of survival in HCC patients with high tumor stage or ETR (P = 0.0026 and P = 0.0002, respectively). Our study indicates the expression of the S100P protein is a novel independent predictor for poor prognosis in HCC, and it is also an unfavorable prognostic predictor in HCC patients with high tumor stage or ETR.